An Analysis of Various Policy Instruments to Reduce Congestion, Fuel Consumption and CO2 Emissions in Beijing - Anas, Alex (2012)
Using a nested multinomial logit model of car ownership and personal travel in Beijing circa 2005, this paper compares the effectiveness of different policy instruments to reduce traffic congestion and CO2 emissions. The study shows that a congestion toll is more efficient than a fuel tax in reducing traffic congestion, whereas a fuel tax is more effective as a policy instrument for reducing gasoline consumption and emissions. An improvement in car efficiency would also reduce congestion, fuel consumption, and CO2 emissions significantly; however, this policy benefits only richer households that own a car. Low-income households do better under the fuel tax policy than under the efficiency improvement and congestion toll policies. The congestion toll and fuel tax require the travel cost per mile to more than triple. The responsiveness of aggregate fuel and CO2 are, approximately, a 1 percent drop for each 10 percent rise in the money cost of a car trip.